The influence of peer assessment on students’ writing scores in descriptive text - Najib, Muhammad Reza Ainun; Trudeau, Liam (Journal of Research in English Language Teaching and Linguistics, 2025)
This study investigates the influence of peer assessment on students’ writing scores in descriptive texts within the context of English as a Foreign Language (EFL) instruction. The importance of enhancing descriptive writing skills is underscored by its critical role in effective communication, particularly in language learning environments where detailed observation and expressive clarity are essential. While existing research has demonstrated the benefits of peer assessment for various writing genres, limited attention has been given to its application in descriptive writing and to students’ subjective experiences during the feedback process. This research addresses this gap by focusing specifically on how peer assessment shapes students’ revision behaviors, perceptions, and writing development in descriptive genres. Employing an exploratory research design, the study involved 24 second-year university students enrolled in an English Education program. Data were collected through pre- and post-writing tasks, structured peer assessment sheets, and guided reflections from participants. The analysis combined textual comparison of writing samples, thematic interpretation of feedback and reflection data, and quantitative examination of score changes, allowing for a comprehensive understanding of both performance outcomes and learners’ cognitive and emotional responses. The findings reveal significant improvements in students’ descriptive writing scores following peer assessment. Participants reported increased awareness of descriptive features, more strategic revision practices, and positive perceptions of peer feedback’s role in their learning process. The study highlights that peer assessment not only enhances writing performance but also fosters critical reflection and learner autonomy. These findings suggest that incorporating structured peer review processes can be an effective pedagogical strategy in EFL writing instruction, especially for genres demanding detailed and expressive language. The implications emphasize the need for educators to adopt multifaceted assessment approaches that integrate peer feedback to promote deeper engagement, independent thinking, and ongoing improvement in descriptive writing skills.